Perlindungan Hukum Bagi Pihak Ke-Tiga Terkait Tindakan Pengurusan dan Pengawasan Yang Dilakukan Direksi Dan/Atau Komisaris Yang Masa Jabatannya Telah Habis - Sharon, Sharon; Widjajaatmadja, Dhody AR; Tondy, Cicilia Julyani (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the legal responsibilities of directors and/or commissioners whose terms of office have expired in managing and supervising companies and examine the legal protection for third parties involved in civil agreements with such directors or commissioners. This study uses a normative juridical research method to review primary, secondary, and tertiary legal materials through statutory, conceptual, analytical, and case approaches. The results indicate that legal actions taken by directors or commissioners whose expired terms are considered legally invalid unless ratified through a General Meeting of Shareholders (GMS). In cases where third parties suffer losses due to such actions, the directors and commissioners are personally liable. Preventive legal protection can be achieved by ensuring the legality of corporate documents before entering into agreements, while repressive protection includes filing lawsuits in court. This study recommends the importance of ratifying legal actions taken by demissionary directors or commissioners to maintain legal certainty and protect the interests of third parties.